Exposure to air boosts CuAAC reactions catalyzed by PEG-stabilized Cu nanoparticles. Issue 39 (2nd May 2017) - Fu, Fangyu; Martinez, Angel; Wang, Changlong; Ciganda, Roberto; Yate, Luis; Escobar, Ane; Moya, Sergio; Fouquet, Eric; Ruiz, Jaime; Astruc, Didier
Abstract : The catalytic activity of Cu(0) NPs is boosted upon aerobic oxidation, forming Cu2 O NPs, and further improved on an SBA-15 support. Abstract : New PEG-stabilized CuNP catalysts are designed upon Cu(ii ) reduction with sodium naphthalenide in MeCN followed by simple purification using the salting-out effect. Their catalytic activity in CuAAC is boosted upon 30 min exposure to air, producing Cu2 O NPs. These NPs are also supported on SBA-15, providing excellent recyclable heterogeneous catalysts that are applied in low amounts for efficient "click" functionalization.